Assessing the Impact of Water Insecurity on Maternal Mental Health at Six Nations of the Grand River - Sultana, Afroza; Wilson, Julie; Martin-Hill, Dawn; Davis-Hill, Lori; Homer, Janet (Frontiers in Water, 2022)
Abstract: The Haudenosaunee or Six Nations (SN) is a matrilineal society sustained through reciprocal relationships with nature and all creation (Hill, 2017). Haudenosaunee hold a special relationship and responsibility with water, as it is the first environment of humans (Cook, 2008). Colonialism attacked Haudenosaunee land, women, children, and traditional ways of life. The Haudenosaunee were displaced from their land and were forced to migrate to a reserve. Colonial and capitalist agendas contaminated water leaving the Six Nations, Canada’s most populated reserve, without clean running water and making SN women and children more vulnerable to water insecurity. The Ohneganos, an SN community project, is intersectional, and the intersectionality of health, culture and water identified maternal health as understudied in water insecurity research. Research on Indigenous mental health mainly focused on suicide and substance abuse and ignored the root causes of violent colonial structures and policies such as the Indian Act and residential schools (Nelson and Wilson, 2017). Our research suggests that gender, migration and water for Indigenous communities must be contextualized with larger violent colonial structures such as environmental racism and epistemic violence. Ohneganos research examines impacts of water insecurity on maternal health and co-developed design and implementation with Six Nations Birthing Centre (SNBC). The SNBC’s traditional Haudenosaunee health care practices shaped the research, revealing the critical importance of community-led research’s efficacy. Haudenosaunee and anthropological research methods are employed to assess the impact of water insecurity on maternal mental health. The co-designed semi-structured interviews highlight the voices of 54 participants consisting of mothers (n=41), grandparents (n=10), and midwives (n=3) of SN. Most participants expressed that the lack of clean water had profound impacts on mental health and had recurring thoughts about the lack of clean water in the SN community. Mental health issues, including depression and anxiety, were reported due to a lack of running water. Despite experiencing water insecurity, Haudenosaunee women demonstrate resiliency through culturally innovative adaptations to their changing environment.